Influence of tobacco use on cataract development. Issue 11 (12th July 2006) - Raju, P; George, R; Ve Ramesh, S; Arvind, H; Baskaran, M; Vijaya, L
Abstract : Aim: To study the influence of tobacco use on cataract formation in a rural South Indian population. Methods: 3924 subjects from the Chennai Glaucoma Study conducted in rural south India underwent a comprehensive eye examination, including Lens Opacities Classification System II grading. Information on tobacco use, type of tobacco (smoking and smokeless), duration and quantity of use was collected. Results: 1705 (male:female (M:F) 1106:599) people used tobacco and were significantly older (mean (standard deviation (SD)) age 55.80 (10.64) years) than non-users (52.23 (10.51); p<0.001). 731 (M:F 730:1) people smoked, 900 (M:F 302:598) used smokeless tobacco, and 74 (M:F, 74:0) used tobacco in both forms. The unadjusted and adjusted (age and sex) odds ratio (OR) for a positive history of tobacco use and cataract was 1.72 (95% confidence interval (CI) 1.51 to 1.96) and 1.39 (95% CI 1.15 to 1.68), respectively. The unadjusted OR for smokers and smokeless tobacco users was 1.04 (95% CI 0.88 to 1.23) and 2.74 (95% CI 2.31 to 3.26), respectively. The adjusted OR was 1.19 (95% CI 0.89 to 1.59) and 1.54 (95% CI 1.22 to 1.95), respectively. No significant association was noted between smoking and any particular type of cataract. Smokeless tobacco use was found to be significantly associated with nuclear cataract even after adjusting for age and sex (OR 1.67, p = 0.067, 95% CI 1.16 to 2.39). Conclusion: Tobacco use was significantly associated with cataract. Smoking was not found to be significantly associated with cataract formation; however, smokeless tobacco use was more strongly associated with cataract.